ANALISIS STRATEGI UNIT USAHA PESANTREN DALAM MENINGKATKAN KESEJAHTERAAN GURU DALAM PERSPEKTIF MAQASHID SYARI’AH (Studi pada Pondok Pesantren Modern Al-Kinanah Jambi) - Halimah Halimah; Eja Armaz Hardi; Maulana Hamzah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Islamic boarding schools are traditional Islamic educational institutions in Indonesia that grow and develop in society. Apart from having a role in Islamic religious education, Islamic boarding schools have a role in improving the economy. The business unit is a forum for Islamic boarding schools to be able to develop an independent economy and be able to provide welfare for teaching and education staff. The aim of this research is to determine and analyze business unit strategies in improving the welfare of teachers at the Al-Kinanah modern Islamic boarding school from a maqashid sharia perspective. The method used is qualitative with data collection methods using observation, interviews, documentation and strategic analysis through SWOT analysis. The informants in this research were Islamic boarding school secretaries, business unit managers and teachers. Based on the research results, it shows that the business unit's strategy is to involve teachers to contribute directly to the business unit. Meanwhile, teachers who work at the Al-Kinanah Islamic boarding school are already prosperous, because the indicators in maqasid sharia have been met. Gratitude is the key for teachers who work in Islamic boarding schools. The business unit's obstacles are the position of the canteen which is not strategic and the condition of the canteen room which is less supportive and adequate.